Life Cycle Portfolio Choice: A Swiss Perspective - Florian Zainhofer (Swiss Journal of Economics and Statistics, 2007)
We use panel data from the Swiss Labor Force Survey to estimate age-earnings profiles as well as transitory and permanent income shock variances for investor groups distinguished by gender, education and activity rate. Estimation results are then used to stylize several different Swiss investor types. Finally, we determine optimal life cycle consumption, savings and risky asset share for these investor types using a recent computational life cycle model of portfolio choice suggested by Cocco et al. (2005). We are particularly interested in the allocation differences between investor types and their normative implications.
Keywords: G11; D14; D91; H55; 330; Personal finance; financial planning; life cycle model; portfolio choice